Soil mapping based on landscape classification in the semiarid Chaco, Argentina - Angueira, Maria Cristina; Cruzate, Gustavo Adolfo; Zamora, Eduardo Maximo; Olmedo, Guillermo Federico; Sayago, J.M.; Castillejo González, Isabel Luisa (Springer, 2017)
The semiarid Chaco is an ecosystem shared by Argentina, Paraguay, Bolivia, and Brazil where land use changes from forest to commercial agriculture and social conflicts have been intensive during the last decade. These changes and the lack of reliable soil information at suitable scales are threatening the sustainable development of the region. In Santiago del Estero province, Argentina, a soil survey was carried out with the objective of reducing the knowledge gap. Due to the large area, geomorphology diversity, limited funding, and high demand of information, a geopedologic survey using remote sensing and GIS was considered an appropriate approach. Map units were determined based on the integration of geoforms and soils, knowledge of landscape and soil forming factors, field observations, and laboratory determinations. Three main landscape units were recognized: (1) a fluvio-eolian Chaco plain including a megafan with Haplustolls and Torripsamments, (2) the Rio Dulce valley with Torripsamments, and (3) the alluvial migratory plain of Río Salado with Torripsamments, Ustifluvents, and Natraqualfs. The used approach helped speed up the soil information collection at appropriate scale for land use planning